2020
DOI: 10.1021/acsinfecdis.0c00545
|View full text |Cite
|
Sign up to set email alerts
|

Feleucin-K3 Analogue with an α-(4-Pentenyl)-Ala Substitution at the Key Site Has More Potent Antimicrobial and Antibiofilm Activities in Vitro and in Vivo

Abstract: The development of antimicrobial compounds is now regarded as an urgent problem. Antimicrobial peptides (AMPs) have great potential to become novel antimicrobial drugs. Feleucin-K3 is an α-helical cationic AMP isolated from the skin secretion of the Asian bombinid toad species Bombina orientalis and has antimicrobial activity. In our previous studies, amino acid scanning of Feleucin-K3 was performed to determine the key site affecting its activity. In this study, we investigated and synthesized a series of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The integrity of the cell membrane was further detected by measuring the leakage of intracellular substances like proteins and nucleic acids. [ 20 ] The content of proteins and nucleic acids in the supernatant showed a dose‐dependent increase after cultivation with varying concentrations of compound 9e (Figures 7A—C). Compared to untreated cells, the OD 260 value of nucleic acids in E. faecalis group obviously increased from 0.07 to 0.35 (Figure 7A) and the leaked protein level also augmented significantly from 0.1 μg/mL to 6.4 μg/mL upon treatment with active compound 9e (8 μg/mL) (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…The integrity of the cell membrane was further detected by measuring the leakage of intracellular substances like proteins and nucleic acids. [ 20 ] The content of proteins and nucleic acids in the supernatant showed a dose‐dependent increase after cultivation with varying concentrations of compound 9e (Figures 7A—C). Compared to untreated cells, the OD 260 value of nucleic acids in E. faecalis group obviously increased from 0.07 to 0.35 (Figure 7A) and the leaked protein level also augmented significantly from 0.1 μg/mL to 6.4 μg/mL upon treatment with active compound 9e (8 μg/mL) (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Many reports showed that peptides with reasonably modulated α-helical structures displayed great selectivity against prokaryotic and eukaryotic cells [19]. In our previous study, K59 was an analog of the α-(4-pentenyl)-Ala substitution that took place in the fourth position [12]. K70 exhibited significant antimicrobial activity without hemolytic activity, whereas K59 showed nonnegligible hemolytic activity at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-activity relationship studies have demonstrated that the key site is the fourth residue, and the antimicrobial activity shows significant enhancement when it is replaced with alanine [11]. In addition, after α-(4-pentenyl)-Ala, an unnatural hydrophobic amino acid, was introduced as the fourth residue, both the antimicrobial activity and stability improved greatly [12].…”
Section: Introductionmentioning
confidence: 99%
“…DMSO was used as a control. Appearance and integrity of the skin were inspected after 16 h. The mouse skin infection model was performed according to our previously described methods . Briefly, two symmetrical circular wounds (5 mm in diameter) were cut on the dorsal surfaces, followed by an injection of 10 μL of bacterial suspension (5 × 10 6 cfu/mL, n = 8).…”
Section: Methodsmentioning
confidence: 99%
“…); action mechanisms of K122 (Figure S4); molecular dynamics of K3 and K122 interacting with the Grampositive membrane POPE/POPG (1:3) lipid bilayers (Supporting video 1 and 2); structure of sulfono-γ-AApeptide building blocks; 1 H and 13 C NMR spectra of sulfono-γ-AApeptide building blocks; MS and HPLC data for synthetic peptides in this study (PDF) (PDF) (PDF) (PDF) (PDF) (…”
Section: S3mentioning
confidence: 99%